Abonad vuestros cafetales: la recuperación de la fertilidad de los suelos del Valle Central de Costa Rica (1870-1915) - Naranjo Gutiérrez, Carlos (2012)
This article analyzes the evolution of soil fertility Depression Central Tectonics, known as the Central Valley of Costa Rica. From the first plantings coffee, occurred in the second decade of the nineteenth century until the late 1870s, coffee production went smoothly implement engineering, farming methods and changes in land use. However, things  began to change following the crisis of 1878, first began with the application of organic fertilizers, chemi cals and nutrients after the end of the century with the introduction of new agricultural practices. The analysis is supported by a reading from multiple sources such as newspapers, agricultural journals, reports the National Society of Agriculture and Department of Agriculture. At the same time, do a scan to the first research and experimentation of fertilizer use.